Charismatic christianity as primal spirituality? - Jurekovič, Igor (Poligrafi, 2025)
The global emergence of Charismatic Christianity ought to be regarded as one of the most consequential phenomena in contemporary history. With estimates reaching as high as 700 million adherents, Charismatics from various denominations have heralded the emergence of Global Christianity. Their considerable popularity has prompted numerous scholarly analyses aimed at elucidating the factors contributing to the emergence of Charismatic Christianity. Social scientists often elaborate on functionalist explanations, suggesting that the popularity of Charismatics can be understood through varying responses to social modernisation. Such explanations, however, frequently neglect the theological innovations inherent to Charismatic Christianity, which garners greater focus from theologians. Among them, Harvey Cox notably asserted that the widespread appeal of Charismatic Christianity can be attributed to its embodiment of experiential primal spirituality. Cox elaborated on three dimensions of Charismatic Christianity as a manifestation of primal spirituality: primal speech, primal piety, and primal hope. The objective of this article is to elucidate Cox’s argument and to examine the advantages of this approach while also offering insights derived from fieldwork conducted among Charismatics in Slovenia. The article posits that Cox’s approach merits appreciation among social scientists, as it identifies unique characteristics of Charismatic spirituality, while also acknowledging its limitations.
Keywords: karizmatično krščanstvo; prvinska duhovnost; religija; religijske spremembe; Slovenija